2021
DOI: 10.1097/scs.0000000000008256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sagittal and Vertical Changes in Maxillary Dental, Skeletal, and Soft Tissue Following Surgically Assisted Rapid Maxillary Expansion: A Retrospective Longitudinal Study

Abstract: Objective: To evaluate whether the maxillary complex would be sagittally, vertically, or mutually displaced after the transverse maxillary correction by surgically assisted rapid maxillary expansion and how the facial profile would be affected. Materials and Methods: The sample comprised 28 adult patients (mean age 25.8 [age range 19-39 years]; 50% women) with transverse maxillary deficiency greater than 7 mm who underwent the surgical rapid maxillary expansion. Cephalometric analysis (n ¼ 112), intra-and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In addition, another seven articles were included after being referenced by the included articles. Ultimately, after undergoing a comprehensive assessment based on the predetermined inclusion criteria, a total of 7 articles were deemed eligible and subsequently included in the final analysis [9,11,[14][15][16][17][18]. The other 19 articles were excluded due to the following reasons: nine lacked maxillary cephalometric measurements [8,13,[20][21][22][23][24][25][26]; three were focused on nonsurgical RPE [27][28][29]; three included patients with orthodontic tooth movement between the two time points of obtaining radiological images [10,30,31]; two were systematic reviews [32,33]; one was reported again in a later study by the same team [34]; and one was a case series with limited sample size [35].…”
Section: Literature Searching and Study Selectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, another seven articles were included after being referenced by the included articles. Ultimately, after undergoing a comprehensive assessment based on the predetermined inclusion criteria, a total of 7 articles were deemed eligible and subsequently included in the final analysis [9,11,[14][15][16][17][18]. The other 19 articles were excluded due to the following reasons: nine lacked maxillary cephalometric measurements [8,13,[20][21][22][23][24][25][26]; three were focused on nonsurgical RPE [27][28][29]; three included patients with orthodontic tooth movement between the two time points of obtaining radiological images [10,30,31]; two were systematic reviews [32,33]; one was reported again in a later study by the same team [34]; and one was a case series with limited sample size [35].…”
Section: Literature Searching and Study Selectionsmentioning
confidence: 99%
“…The risk of bias assessment (Table 2) was conducted on all seven articles to ascertain their strength of evidence. Based on this evaluation, three of the studies were identified as having a medium risk of bias [16][17][18], while the other four studies were deemed to have a high risk of bias [9,11,14,15]. The most common sources of bias were "sample randomization" and "blind assessments".…”
Section: Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…These movements can cause the mandible to rotate backward and downward, resulting in an increase in facial height. It has been reported that RME can also cause changes in soft tissues due to the movements in the maxillary segments and maxillofacial sutures [16][17][18][19]. Furthermore, studies utilizing posteroanterior radiographs have reported increases in nasal, maxillary and zygomatic width following RME, reflecting changes in hard tissues [18,20,21].…”
Section: Introductionmentioning
confidence: 99%